Alternative Access for Transcatheter Aortic Valve Implantation: Current Evidence and Future Directions - JJ Coughlan (Radcliffe Medical Media, 2019)
Transcatheter aortic valve implantation (TAVI) is the usual technique for patients with severe aortic stenosis who are at high risk for surgical aortic valve replacement. The transfemoral (TF) route is the most commonly used access type, and significant progress in this procedure has greatly increased the proportion of patients who can undergo it. Not all patients are suitable for TF TAVI, however, so other routes, including transapical, transaortic, subclavian, trans-subclavian/transaxillary, transcarotid and transcaval, may need to be used. Evidence on these routes shows promising results but the majority of this is registry data rather than randomised controlled trials, so TF TAVI remains the safest access route and should be considered for most patients. However, in patients who are unsuitable for TF TAVI, alternative access routes are safe and feasible. The challenges concern choosing the best route, the valve to use and skill of the specialist centre. This article provides a overview of options for alternative vascular access in TAVI, the clinical rationale for using them, current evidence and areas for clinical investigation.